Evaluation of the reasons for the microvascular changes in patients with Fabry disease using optic coherence tomography angiography. Issue 6 (November 2021) - Dogan, Cezmi; Gonen, Busenur; Dincer, Mevlut Tamer; Mergen, Burak; Kiykim, Ertugrul; Bakir, Alev; Trabulus, Sinan; Yetik, Huseyin; Seyahi, Nurhan
Purpose: To investigate the blood flow changes in the choriocapillaris and the superficial and deep capillary plexus of the retina using optic coherence tomography angiography (OCTA) in patients with Fabry disease (FD) and reveal any possible association of these changes with the systemic findings. Methods: This cross-sectional study included 38 patients with FD and age- and gender-matched 40 healthy controls. OCTA images were obtained from all patients. Superficial (sCVD) and deep capillary vascular density (dCVD) in the foveal, parafoveal, and perifoveal zones and the whole image were recorded for each patient. Flow area in the choriocapillaris and central macular thickness (CMT) were also recorded. Results: Patients with FD showed a lower whole image (54.45 ± 5.99% vs 57.32 ± 6.71%, p = 0.004), foveal (34.94 ± 7.60% vs 39.65 ± 7.03%, p = 0.003), parafoveal (57.41 ± 4.85% vs 59.19 ± 4.67%, p = 0.043), and perifoveal (55.87 ± 6.43% vs 58.87 ± 7.02%, p = 0.003) dCVD compared to the healthy controls without a significant difference in the sCVD and choriocapillaris blood flow ( p > 0.05). A significantly lower whole image and foveal dCVD in the FD patients with renal involvement was observed compared to the healthy controls ( p = 0.027 and p = 0.024, respectively) without any significant difference between the FD patients without renal involvement and healthy controls ( p = 0.17 and p = 0.13, respectively). CMT was significantly higher in FD patients with renal involvement compared to the ones without renal involvement (252.1 ± 18.5 µm vs 235.5 ± 17.6 µm, p = 0.016). Conclusion: Patients with FD showed a lower dCVD without any change in sCVD and choriocapillaris compared to the healthy controls. This decrease was associated mostly with the renal involvement and duration of treatment.